Rietveld quantitative phase analyses of SRM 2686a: a standard Portland clinker - García-Maté, Marta; Álvarez-Pinazo, Gema; León-Reina, Laura; Gómez-de-la-Torre, María de los Ángeles (My University, 2018)
SRM 2686a is a NIST reference Portland clinker with reported mineralogical analysis from powder diffraction and electron microscopy. This sample is used in ASTM C1365 test method for Rietveld quantitative phase analysis validation procedure. Here, we have analysed SRM 2686a by using three state-of-the-art powder diffraction configurations: i) strictly monochromatic CuKα 1 radiation in flat reflection geometry; ii) strictly monochromatic MoKα 1 radiation in flat transmission geometry; and iii) synchrotron radiation in rotating capillary transmission geometry. The silicate and aluminate enriched residues have also been studied by CuKα 1 powder diffraction. All the powder patterns were analysed by Rietveld method with the best available protocols. The results indicate that belite in SRM 2686a is composed of two polymorphs (- and α’H-) that must be included in the analyses. The use of a unique phase for describing belite (-polymorph) and improper peak shape modelling could explain the problems found for implementing ASTM C1365 in some cement manufacturing plants. Furthermore, all the patterns are deposited as open data access at Zenodo, so interested laboratories can analyse these data to verify their protocols.
Keywords: Radiación sincrotrónica; Mineralogía; Mineralogical content; Synchrotron radiation; Powder diffraction; Reference material